(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The aim of this research is to determine how well the Cubing Technique affects the Iraqi EFL students’ composition writing, vocabulary, and meta-cognitive awareness of writing strategies. The sample of (64) secondary-school female students in the fifth grade is drawn from two classrooms and split into two equal groups: the experimental group and the control group, each of which consists of (32) students. A quasi-experimental design is applied. The performance test and Meta-cognitive Writing Strategies questionnaire are given as a pre-test for equalizing the two groups after ensuring their validity and reliability. Then, they are administrated as a posttest in both groups. According to the results, the significant differences are in favor of the cubing technique. Therefore, it is recommended to use it in teaching English as a foreign language.